Membangun Umat dengan Pemahaman Al-Qur'an yang Toleran dan Moderat Strategi Melalui Pendekatan Pendidikan dalam Keluarga - Muhammad Darwis Hude (SUHUF, 2008)
This writing puts its emphasis on the importance of education in the family since the family is the smallest unit in society. In addition to that; in the formal educations, the children get from the school only give standard service, whereas each child has a very special and unique character and different level of intelligence. There are three models of upbringing education, they are: authoritarian model, democratic model, and permissive model. Shifting paradigm in the family is needed to be done, that is from "Parents oriented" to. "Children oriented". Further, in relation to Islamic education, some internalization stages of the Qur'anic values in the family are: the first is through the stage of habituation of the Qur 'anic values, the second is through the stage of identification of the Qur 'anic values, and the third is the stage of crystallization of the Qur'anic values.